Increased risk of cancer mortality by smoking-induced aryl hydrocarbon receptor repressor DNA hypomethylation in Japanese population: A long-term cohort study. (June 2022) - Tsuboi, Yoshiki; Yamada, Hiroya; Munetsuna, Eiji; Fujii, Ryosuke; Yamazaki, Mirai; Ando, Yoshitaka; Mizuno, Genki; Hattori, Yuji; Ishikawa, Hiroaki; Ohashi, Koji; Hashimoto, Shuji; Hamajima, Nobuyuki; et al.
Abstract: Background: Smoking is well known to be a major risk factor for cancer, and to decrease the levels of aryl hydrocarbon receptor repressor ( AHRR ) DNA methylation. AHRR is a key regulator for AHR signaling, which is involved in chemical metabolism and cancer development. Therefore, smoking-induced AHRR DNA hypomethylation may be associated with cancer development. However, it has not been reported that association between AHHR DNA methylation and cancer mortality in Asian population. Hence, we examined whether AHRR DNA methylation levels were associated with cancer mortality in a Japanese population. Methods: This study was conducted with 812 participants (aged 38–80 years) who received a health check-up in 1990, and did not have a clinical histories. We followed up the participants until the end of 2019 (median: 27.8 years), and 100 participants died from cancer. The AHRR DNA methylation levels in peripheral blood mononuclear cells (PBMCs) were measured by the pyrosequencing method. We calculated the hazard ratio (HR) and 95% confidence interval (CI) for cancer mortality according to the baseline levels of AHRR DNA methylation. Results: We found that AHRR DNA hypomethylation was associated with a higher risk of all cancer mortality, especially smoking related cancers and lung cancer. (all cancer: HR, 1.28, 95% CI, 1.09–1.51; smoking-related cancers: HR, 1.35, 95% CI, 1.12–1.62; lung cancer: HR, 1.68, 95% CI, 1.24–2.26). Conclusions: Smoking-induced AHRR DNA hypomethylation in PBMCs was associated with the risk of cancer mortality in Japanese population; therefore, hypomethylation of AHRR may be a useful biomarker of cancer mortality risk. Highlights: DNA methylation is presumed to be useful for estimating the risk of cancers. Smoking exposure induces AHRR hypomethylation. The association between AHHR methylation and cancer is not clear in Asian. We showed AHRR hypomethylation increased risk for cancer in a Japanese population. Hypomethylation of AHRR may be a useful marker of cancer mortality risk.